Population dynamics of Chaetocnema tibialis Illiger and Phyllotreta vittula (Redtenbacher) on the weed Amaranthus retroflexus L. and cultivated Amaranthus caudatus L. - Ľudovít Cagáň; Peter Tóth; Monika Tóthová (Plant Protection Science, 2006)
In 1995-1997, the population dynamics of the flea beetles Chaetocnema tibialis and Phyllotreta vittula, associated with Amaranthus retroflexus (wild species) and Amaranthus caudatus (cultivated species), were studied at the locality Nitra-Malanta (48°19'N, 18°09'E) in south-western Slovakia. On both plant species, the number of C. tibialis adults was usually very low until the beginning of July. During July the number of C. tibialis increased, but sooner on cultivated amaranth. An increased number of C. tibialis adults was observed on both amaranth species until the middle of September. The results showed that amaranth plants are a very important reservoir of C. tibialis during summer. P. vittula was a common flea beetle on amaranth during the whole summer, but its numbers never exceeded more than 10 adults per 25 plants. Low temperatures in winter had a negative effect on populations of C. tibialis on both amaranth species and also on populations of P. vittula on A. retroflexus. The lower the precipitation was in July, the higher were the populations of C. tibialis on both amaranth species and the populations of P. vittula on A. retroflexus.